Sosialisasi Pengelolaan Limbah Medis B3 di RSUD Batara Guru - Sosiawan, Insan; Zamli (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This community service activity aims to increase understanding and awareness of hazardous and toxic medical waste management (B3) at Batara Guru Regional Hospital, Luwu Regency. The main problem encountered was a lack of technical understanding and implementation of regulatory waste management standards. The activity was implemented through interactive outreach with pre- and post-tests to measure participants' knowledge. Results showed significant improvement, with knowledge in the good category increasing from 22.73% to 90.91%. This activity demonstrates the importance of regulation-based and participatory education in fostering a safe and healthy work culture in hospitals.